1991
DOI: 10.2151/jmsj1965.69.1_15
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Diffusional Growth of Free-Falling Snow Crystals between -3 and -23°C

Abstract: The characteristics of snow crystal growth by vapor diffusion at water saturation and in free fall were quantitatively investigated in a vertical supercooled cloud tunnel for periods up to 30 min at temperatures from -3 to -23*.The results obtained are as follows: 1) the basic growth habits were plates (>-4.0*), columns (-4.0--8.1*), plates (-8.1--22.4*) and columns (<-22.4*), respectively. At about -5.5, -12, -14 .5, -16.5 and -18*, crystal shapes were enhanced with time; 2) for an isometric crystal, the slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
142
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(151 citation statements)
references
References 22 publications
(31 reference statements)
6
142
2
1
Order By: Relevance
“…The same subfreezing temperature at low latitudes corresponds to a higher height above mean sea level and therefore a lower atmospheric pressure level than mid-and high latitudes. Takahashi et al (1991) show that the mass growth rate at 860 mb is approximately 30 % larger than at 1010 mb due to the impact of pressure difference on the diffusivity of water vapor in air. It is also noted that, from Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The same subfreezing temperature at low latitudes corresponds to a higher height above mean sea level and therefore a lower atmospheric pressure level than mid-and high latitudes. Takahashi et al (1991) show that the mass growth rate at 860 mb is approximately 30 % larger than at 1010 mb due to the impact of pressure difference on the diffusivity of water vapor in air. It is also noted that, from Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The type of ice crystals is determined depending on temperature range where the particles arise (Takahashi et al, 1991). Secondary ice generation is taken into account during riming (Hallett and Mossop, 1974).…”
Section: Model Descriptionmentioning
confidence: 99%
“…At higher temperatures, might differ significantly from unity and strongly impact the evolution of the aspect ratio (ϕ = c/a) of an ice particle that develops from the initial geometry, prescribed by , towards a geometry as predicted at a given temperature. Such more extreme habits result in highly nonlinear growth rates of ice particles in different temperature regimes since non-spherical particles grow faster than spheres of the same mass (Mason, 1953;Takahashi et al, 1991). Atmospheric observations reveal that ice is sometimes formed at habit-prone temperatures and model studies have shown the need of the detailed description of ice growth rates as they significantly affect the phase partitioning in mixed-phase clouds (Avramov and Harrington, 2010;.…”
Section: Temperature Dependence Of Ice Habit Formationmentioning
confidence: 99%